Marginal Damage Cost of Nutrient Enrichment - The Case of the Baltic Sea - Nguyen, Thanh Viet (ĐHKT, 2016)
The purpose of the article is to investigate the link between pollution and marine renewable resources. A bio-economic model of a fishery is developed to derive a marginal damage function for nutrient enrichment using the dynamic production function approach…